2023
DOI: 10.1002/ejoc.202300090
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Free, Heating‐Induced Desulfurization Annulation of CF3‐Imidoyl Sulfoxonium Ylides with Isothiocyanates for the Synthesis of 2‐Trifluoromethyl‐4‐aminoquinolines

Abstract: A heating‐induced desulfurization annulation of readily available CF3‐imidoyl sulfoxonium ylides and isothiocyanates for the construction of 2‐trifluoromethylquinolines has been achieved. The developed transformation was performed under metal‐ and additive‐free conditions, producing a variety of biologically valuable 2‐trifluoromethylquinoline derivatives with high efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…We then screened of solvents, and found that TBME improved the yield to 40%. We also noticed that 4‐aminoquinoline 7 was formed as the major byproduct in the above mentioned reactions (entries 1–5) [10b] . The addition of bases such as triethylamine, Na 2 CO 3 and K 2 CO 3 , did not give a better result (entries 6–8), while acids as additives only led to trace amounts of product formation (entries 9, 10).…”
Section: Resultsmentioning
confidence: 91%
“…We then screened of solvents, and found that TBME improved the yield to 40%. We also noticed that 4‐aminoquinoline 7 was formed as the major byproduct in the above mentioned reactions (entries 1–5) [10b] . The addition of bases such as triethylamine, Na 2 CO 3 and K 2 CO 3 , did not give a better result (entries 6–8), while acids as additives only led to trace amounts of product formation (entries 9, 10).…”
Section: Resultsmentioning
confidence: 91%
“…The intramolecular cyclization of B afforded an unstable 3‐membered ring intermediate C , followed by desulfurization process to give ketenimine intermediate D . [ 14 ] Then, an intramolecular Friedel−Crafts cyclization or electrocyclization of D occurred to lead to anion E . Finally, the protonation of E could deliver the desired 4‐aminoquinoline product 3 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 12 ] Furthermore, the cascade annulation reactions employing TFISYs as multifunctional building blocks with suitable partners have successfully furnished various trifluoromethyl‐decorated heterocycles, including pyrroles, pyridones, pyrazoles, benzo[ b ][1,4]oxazines, 2,3‐dihydrothiazoles and 1,4‐dihydro‐1,2,4‐triazines. [ 13 ] Very recently, our group developed a heating‐induced desulfurization annulation of TFISYs and isothiocyanates for the preparation of 2‐trifluoromethyl quinolines, [ 14 ] whereas the isothiocyanates should be pre‐synthesized and substrate scope of the reaction was relatively limited. It is found that TFISYs could be applied as 1‐, 3‐ or 5‐atom synthons to build structurally diversified CF 3 ‐containing heterocycles.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…In consideration of the high reactivity of TFISYs and the precedent work about the silver-catalyzed reaction of isocyanides with sulfoxonium ylides, 64 a heating-induced desulfurization annulation of TFISYs and isothiocyanates for the construction of biologically valuable 2-trifluoromethyl-4-aminoquinolines was presented by Wu, Chen and co-workers (Scheme 51). 65 The simple transformation was performed under catalyst- and additive-free conditions, which had many advantages of easy operation, insensitivity to air and moisture, high efficiency and scalibility. The benzoyl isothiocyanate was also suitable for the reaction system, but isocyanatobenzene did not work under the standard conditions.…”
Section: Synthesis Of Cf3-containing Heterocycles From Cf3-imidoyl Su...mentioning
confidence: 99%